2012
DOI: 10.1111/j.1469-0691.2012.03940.x
|View full text |Cite
|
Sign up to set email alerts
|

The spread of vaccine-preventable diseases by international travellers: a public-health concern

Abstract: Vaccine-preventable diseases (VPDs) are costly at both the individual and societal levels. The most common VPDs recorded in travellers are enteric (typhoid or paratyphoid B) fever, acute viral hepatitis, influenza, varicella, measles, pertussis and bacterial meningitis. Travellers suffering from VPDs are frequently hospitalized, illustrating the point that VPDs are serious and expensive. Many travellers are not properly immunized before travel. In addition to individual consequences, VPDs can have public-healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 54 publications
0
30
0
1
Order By: Relevance
“…This process is facilitated when the environmental conditions in different parts of the world share common characteristics ( 36 ). Meanwhile, numerous vaccine-preventable diseases, such as polio, meningitis or measles, can also be introduced or reintroduced to susceptible populations as a consequence of international travel ( 39 ).…”
Section: Infectious Disease Drivers and Interconnected Riskmentioning
confidence: 99%
“…This process is facilitated when the environmental conditions in different parts of the world share common characteristics ( 36 ). Meanwhile, numerous vaccine-preventable diseases, such as polio, meningitis or measles, can also be introduced or reintroduced to susceptible populations as a consequence of international travel ( 39 ).…”
Section: Infectious Disease Drivers and Interconnected Riskmentioning
confidence: 99%
“…Types of threats and the pathogens involved shift in relation to changing factors such as climate change [1,2], global travel and trade [3,4], immigration patterns, urban sprawl, social inequalities [5,6] and other disease drivers [7][8][9][10]. An increasingly interconnected world means that diseases emerging in one part of the world, such as Zika, Middle East respiratory syndrome coronavirus or Ebola [11,12] can spread globally.…”
Section: Introductionmentioning
confidence: 99%
“…The most common vaccines are against typhoid fever, acute viral hepatitis, influenza, varicella, measles, pertussis, and bacterial meningitis. 21 A study by Toovey et al 22 found that 48% and 44% of individuals considered themselves at risk for hepatitis A and hepatitis B, respectively, considering their destinations. Similarly, a study by Flaherty et al 23 found that travelers had a low level of awareness of travel-related infectious diseases.…”
Section: Discussionmentioning
confidence: 99%